Agama dan Tantangan Pengembangan Masyarakat Multikultur di Indonesia - Nurisda, Deni (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Indonesia is a country full of diversity, with a large population, rich in natural resources, a vast archipelago, and diversity in language and culture. Indonesia has potential as a developing country, but it also has problems that hinder it. One of Indonesia's potentials is that it is a country that has thousands of islands that are plural in nature when viewed from the diversity of religions, human races, tribes living in an area, human creations in the form of cultural customs and arts. Several things, such as the large number of differences, tend to be prone to conflicts and divisions that occur between citizens. In Indonesia, there are about six religions that are officially recognized and recorded and there are local beliefs that are still held by people in various regions. The largest number of adherents of religion in Indonesia is Islam with an estimated number of more than 229 million adherents which, if presented, means that 13% of the world's Muslim adherents are found in Indonesia. The diversity of religious communities that exist in Indonesia with the number of adherents of the Islamic religion which is numerically more (the majority) is often one of the causes of conflicts with religious backgrounds that occur in Indonesia. There are challenges that pose a fundamental threat to a democratic and multicultural country, namely discrimination followed by hatred that arises due to differences in a group (sectarianism). This form of sectarian behavior is characterized by an anti-tolerant attitude towards groups or individuals who are considered to have different views. Several incidents that have occurred in Indonesia, such as: mass actions, destruction of places of worship, clashes between religious communities, issues related to SARA, acts of violence against other religious sects, and other incidents which of course have something to do with anti-tolerance. The emergence of regional regulations (Perda) in several regions which are often similar to those contained in certain religious laws, will often cause problems for countries such as Indonesia which is multicultural and democratic, because Indonesia is not formed from one group, not formed from one religion, one race and one. ethnicity alone, but is formed from various ethnic groups, religions, races and between groups. Not only because the regional regulation is not in accordance with the constitutional hierarchy, but also because the regional regulation is very superficial and not substantial.